THE NEXUS BETWEEN BRAND REPUTATION AND BUSINESS SUSTAINABILITY: A STUDY OF SELECTED SMEs IN SOUTHERN NIGERIA - N, KPUNEE, HENRY; EBERE, OKOCHA, REJOICE; STEPHEN, OTIKA, UDOKA (IJRDO - Journal of Business Management, 2017)
The Nexus between Brand Reputation And Business Sustainability: A Study of Selected SMEs in Southern Nigeria. Data for this study was collected from a primary source using a five point likert questionnaire. Its design followed a descriptive survey and the study covered a sample of 80 SME operators drawn from Portharcourt in Rivers State and Aba in Abia State. The t-test statistic was used to test the two hypotheses stated in this study with the aid of statistical software known as SPSS Software version 20.00. Findings from the study reveal that brand awareness and brand loyalty significantly relate with social and economic sustainability of SMEs. The study concludes that for SMEs in southern Nigeria to attain and remain sustainable, there is need to redefine their perception of branding as a mere marketing tool to embrace sustainability programme. Moreover, the engagement of marketing communication experts in their product branding activities can help SMEs in developing the right brand message that can create awareness sustain the loyalty of the customers to their brands